2023
DOI: 10.3390/ijerph20085610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Formal Aquatic Activities on Babies Younger Than 36 Months: A Systematic Review

Abstract: This systematic review investigated the possible effects of exposing infants to formal activities in aquatic environments. A literature search of eight databases was concluded on 12 December 2022. Studies were eligible if they: (i) focused on 0–36 months of age infants, (ii) addressed the exposure of infants to formal aquatic activities, and (iii) compared the ‘same condition of aquatic exposure with the control’ or ‘before and after exposure’. The PRISMA protocol was used. Articles considered for inclusion (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, lower birth weight associated with MPSE reported in other studies was not detected in this cohort. Another contributing factor to the low amount of variance explained by the potential predicting factors of GMQ is that the development of gross motor skills in children is a complex process that is affected by a variety of factors such as child's sleeping time and position 42,43 , exposure to formal aquatic activities 44 , and maternal moderate-to-vigorous intensity physical activity during pregnancy 45 . Moreover, MPSEassociated factors such as duration of breastfeeding may also contribute to differential gross motor skills in children with or without MPSE 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower birth weight associated with MPSE reported in other studies was not detected in this cohort. Another contributing factor to the low amount of variance explained by the potential predicting factors of GMQ is that the development of gross motor skills in children is a complex process that is affected by a variety of factors such as child's sleeping time and position 42,43 , exposure to formal aquatic activities 44 , and maternal moderate-to-vigorous intensity physical activity during pregnancy 45 . Moreover, MPSEassociated factors such as duration of breastfeeding may also contribute to differential gross motor skills in children with or without MPSE 46 .…”
Section: Discussionmentioning
confidence: 99%
“…More than a promotor of aquatic skill competencies, baby swimming programs have been considered for many years a way of entertaining babies, promoting social interactions and opportunities for parents to bond with their infants. Although it has been shown that infants younger than 2 years of age cannot learn swimming or survival skills in the water (Taylor et al, 2020), recent studies have shown other important benefits of (Camus, 1993)baby swimming participation (Santos et al, 2023). For instance, it has been shown that young children who participate in early-years swimming achieve particular motor milestones earlier than the normal population across motor (Borioni et al, 2022;Dias et al, 2013;Leo et al, 2022;Pereira et al, 2011;Sigmundsson & Hopkins, 2010) and cognitive (Borioni et al, 2022) domains.…”
Section: Introductionmentioning
confidence: 99%